Out of the mouths of babes: the -child in Ancient Egypt - Hinson, Benjamin (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
This article presents a case study for approaching the analysis of Ancient Egyptian words which describe aspects of childhood. After a methodological introduction, the Egyptian word will be used as a test case. Whilst is in some way related to childhood, it occurs only once in written evidence, and its specific meaning is unclear. Perhaps because of this, it has received little discussion in literature. However, a re-evaluation of the word suggests that despite its rareness, it is of both etymological and social interest. It will be argued here that is onomatopoeic, used specifically in reference to children of pre-speaking age. Establishing a context within which this word may have been employed in turn offers interesting information about how infancy was understood in Ancient Egypt.